Determination of the Effect of Aeration Rate on Composting of Vegetable-Fruit Wastes - Arslan, E. Isil; Unlu, Ayhan; Topal, Murat (Wiley, 2011)
In this study, it was aimed to determine the effect of various aeration rates on composting to supply the optimum aeration rate for a successful and economic composting. For this aim, vegetable-fruit wastes (VFW) were composted at various aeration rates (0.37, 0.49, 0.62, 0.74, 0.86, and 0.99 L/min kg VS) and moisture, temperature, pH, electrical conductivity, C/N, and cellulose were investigated. Moistures of the reactor that had the highest aeration were generally lower than those of the others. Reactor that had the lowest aeration reached thermophilic phase earlier than the others and stayed more days. This situation was opposite for the reactor that had the highest aeration. pH variations with aeration rates were not significant. Although electrical conductivity did not differ significantly with aeration rates, at the beginning of the thermophilic phase it generally increased with the increase in aeration. The highest C/N reduction was observed in the reactor that had an aeration of 0.62 L/min kg VS. The final cellulose contents were close to each other. It could be said that aeration rates used were efficient on composting of VFW. Taking the C/N into account which is the parameter of the indicator of the stabilization in composting, it could be said that the optimum aeration rate for forced aerobic composting of VFW was 0.62 L/min kg VS.
Keywords: Aeration; Composting; Fruit; Vegetable; Waste